2003
DOI: 10.1007/s00170-002-1441-9
|View full text |Cite
|
Sign up to set email alerts
|

Neural network modeling and analysis of the material removal process during laser machining

Abstract: To manufacture parts with nano-or microscale geometry using laser machining, it is essential to have a thorough understanding of the material removal process in order to control the system behaviour. At present, the operator must use trial-and-error methods to set the process control parameters related to the laser beam, motion system, and work piece material. In addition, dynamic characteristics of the process that cannot be controlled by the operator such as power density fluctuations, intensity distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(40 citation statements)
references
References 13 publications
1
39
0
Order By: Relevance
“…In their work these authors wanted to develop a model which they could use to select the laser processing parameters which would result in the required ablation depth and width of a conical shaped crater. The test results showed that the ANN modelled level of pulse energy corresponding to specific depth and diameter was consistent with the actual level of pulse energy to a high degree of accuracy due to the adaptive properties of ANN [26].…”
Section: Introductionmentioning
confidence: 82%
“…In their work these authors wanted to develop a model which they could use to select the laser processing parameters which would result in the required ablation depth and width of a conical shaped crater. The test results showed that the ANN modelled level of pulse energy corresponding to specific depth and diameter was consistent with the actual level of pulse energy to a high degree of accuracy due to the adaptive properties of ANN [26].…”
Section: Introductionmentioning
confidence: 82%
“…Tables 1-4 further show the comparison of two primary surface roughness parameters, Ra and Rmax, between the MLP and RBF models. The mean squared error shown in these tables is defined as 1/2 (measured value − predicted value) 2 . The smaller the mean squared error, the higher the prediction accuracy.…”
Section: Testing Of Mlp and Rbf Modelsmentioning
confidence: 99%
“…This partially reflects the rarity of technologies that can measure and store temperature and time in some manner without internal or external sources of power. The difficulty is compounded in applications in metallurgy 1,2 , VLSI processing 3,4 and laser machining 5,6 , to name only a few, when the device must be unobtrusive and robust enough to be incorporated in a wide variety of heat treatments at temperatures that will destroy typical nonvolatile electronics.…”
Section: Introductionmentioning
confidence: 99%